2020
DOI: 10.3390/buildings10090148
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mapping of Techno-Economic Performance of a Water-Based Solar Photovoltaic/Thermal (PVT) System for Buildings over Large Geographical Cities

Abstract: Solar photovoltaic thermal (PVT) is an emerging technology capable of producing electrical and thermal energy using a single collector. However, to achieve larger market penetration of this technology, it is imperative to have an understanding of the energetic performance for different climatic conditions and the economic performance under various financial scenarios. This paper thus presents a techno-economic evaluation of a typical water-based PVT system for a single-family house to generate electricity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the context of the rapid increase in global energy demand and recognition of climate change prominence, the need for energy-efficient retrofitting measures (EEMs) to reduce energy use in individual buildings and building stock has become imperative [1]- [3]. Considering the increasing energy prices in Europe in recent months, this need for energy efficiency has never been as important as it is now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of the rapid increase in global energy demand and recognition of climate change prominence, the need for energy-efficient retrofitting measures (EEMs) to reduce energy use in individual buildings and building stock has become imperative [1]- [3]. Considering the increasing energy prices in Europe in recent months, this need for energy efficiency has never been as important as it is now.…”
Section: Introductionmentioning
confidence: 99%
“…π’Œπ‘Ύπ’‰ 𝒕𝒐𝒕𝒂𝒍 = 𝑰𝒏𝒑𝒖𝒕 π’Œπ‘Ύπ’‰ 𝒆𝒍 + 𝑰𝒏𝒑𝒖𝒕 π’Œπ‘Ύπ’‰ 𝒐𝒕𝒉𝒆𝒓(3) User input in bill amount (SEK) and electricity prices. Although the recommended method is to input the energy use in kWh, this benchmark model provides an extra option to input their gross electricity monthly bill amount (Swedish Krona SEK) of anyone latest month in each season.…”
mentioning
confidence: 99%
“…Fayaz et al reviewed the use of a phase change material (PCM) in PVT systems and concluded that the cooling effect increased, owing to the application of the PCM; consequently, the power generation efficiency increased [26]. Reddy Penaka et al reviewed measures to evaluate the economic feasibility of applying PVT based on country-specific climatic conditions, energy consumption and energy cost [27].…”
Section: Introductionmentioning
confidence: 99%